The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1185/030079906x100050
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of armodafinil as treatment for adults with excessive sleepiness associated with narcolepsy

Abstract: Armodafinil significantly improved ability to sustain wakefulness throughout the day in patients with narcolepsy. Armodafinil also significantly improved overall clinical condition, memory, attention, and fatigue when compared with placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
194
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(202 citation statements)
references
References 18 publications
6
194
0
1
Order By: Relevance
“…A more recent multicentre double-blind study with 196 patients by Harsh et al 37 showed that armodafanil (R-modafanil: an enantiomer of the racemic compound modafinil, with a longer half-life of 10-14 hours) significantly increased MWT mean sleep latency compared with placebo. The mean increase from baseline to final visit for armodafinil was 1.3, 2.6 and 1.9 minutes in the 150mg, 250mg, and 150 and 250mg combined groups, respectively, compared with a decrease of 1.9 minutes for placebo (p<0.01 for all three comparisons).…”
Section: Treatment Of Excessive Daytime Sleepinessmentioning
confidence: 99%
“…A more recent multicentre double-blind study with 196 patients by Harsh et al 37 showed that armodafanil (R-modafanil: an enantiomer of the racemic compound modafinil, with a longer half-life of 10-14 hours) significantly increased MWT mean sleep latency compared with placebo. The mean increase from baseline to final visit for armodafinil was 1.3, 2.6 and 1.9 minutes in the 150mg, 250mg, and 150 and 250mg combined groups, respectively, compared with a decrease of 1.9 minutes for placebo (p<0.01 for all three comparisons).…”
Section: Treatment Of Excessive Daytime Sleepinessmentioning
confidence: 99%
“…[37][38][39][61][62][63] A summary of the results of these clinical trials is given in Tables 2 and 3. In addition, there are two ongoing open-label trials of armodafi nil: one in trial-naïve patients (with narcolepsy, OSA, or SWD) and one extension study in patients who completed any of the randomized trials and were able to participate for 12 months or longer.…”
Section: Clinicalmentioning
confidence: 99%
“…Night-time sleep was not affected in patients administered armodafi nil. 37 Obstructive sleep apnea OSA is a sleep disorder characterized by episodes of partial or complete collapse of the airway and is associated with increased morbidity and mortality. 69 The most common symptom of OSA is ES.…”
Section: Narcolepsymentioning
confidence: 99%
See 2 more Smart Citations